2009
DOI: 10.1002/ana.21475
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against β‐amyloid are common in Alzheimer's disease and help control plaque burden

Abstract: Autoantibodies directed against beta-amyloid are common in AD patients and may contribute in controlling plaque burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 31 publications
3
67
0
Order By: Relevance
“…However, natural antibodies against Aβ peptides are present in the sera of AD patients and in non demented individuals [31]. These auto-antibodies inhibit Aβ peptide aggregation in vitro [32], and it has been observed that in non-amyloid-immunized AD patients, auto-antibodies against Aβ peptides may help reduce the plaque burden and increase the numbers of phagocytic microglia [32]. Altogether, these data can be interpreted as an Aβ peptide antibody-dependent activation of immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, natural antibodies against Aβ peptides are present in the sera of AD patients and in non demented individuals [31]. These auto-antibodies inhibit Aβ peptide aggregation in vitro [32], and it has been observed that in non-amyloid-immunized AD patients, auto-antibodies against Aβ peptides may help reduce the plaque burden and increase the numbers of phagocytic microglia [32]. Altogether, these data can be interpreted as an Aβ peptide antibody-dependent activation of immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, one recent study [68] of AD brain tissue suggests that the majority of neuritic plaques in AD brain tissue are decorated by IgG and have a corresponding increase in associated phagocytic microglia.…”
Section: Post Mortem Brain Studiesmentioning
confidence: 99%
“…The foetal Alzheimer antigen (Alz50) which labels taucontaining filaments 56 , and is homologous to these pathogens (Fig 2) is an evident example. There are too many proteins to analyse individually, and beta-amyloid is used as an example, primarily because of the presence of beta-amyloid autoantibodies in the sera of the ageing population 69 and in Alzheimer's disease 38,58 . As seen in Fig 6, the beta-amyloid peptide is studded with vatches from a large number of phages and viruses, many within the immunogenic regions of the peptide.…”
Section: Immunogenic Proteinsmentioning
confidence: 99%